Synthesis of gold nanoparticles using ceftriaxone sodium as a reducing and stabilizing agent - Jameel Abdulghani, Ahlam; Khalil Mohuee, Saja (Iraqi Journal of Science, 2023)
The synthesis of gold nanoparticles AuNPs was achievedby the reduction of sodium tetrachloroaurate (III) (NaAuCl4) with ceftriaxone sodium (CR) in aqueous solutionswithout the use of other reducing agent. The effect of reactants concentration, temperature and pH on the sizes and morphology of AuNPs were also studied. The synthesized AuNPs were characterized by UV- visible spectroscopy, X-ray diffraction (XRD), scanning electron microscope (SEM), and atomic force microscope (AFM) analysis. Conjugation of antibiotic with the nanoparticles was characterized by FTIR spectrophotometry.